Adaptive Optimal Control of the Flapping Rule of a Fixed Flapping Plate (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, with the use of the moving boundary computationalfluid dynamics method, we developed a new real-time optimal controlmethod which can be used to find the optimal flapping mode of afixed flapping plate. The results show that there is a 54.0%increase in the thrust obtained by the unsteady optimal flappingrule. In addition, to reduce the cost of computation and to have abetter understanding of the flapping rule, the maximum velocity atthe end tip of the flapping plate is taken as the objectivefunctional, with which the thrust is increased by 22.9%.